Pupuk Majemuk dan Pemupukan Hara Spesifik Lokasi pada Padi Sawah - Zulkifli Zaini (Puslitbang Tanaman Pangan, 2012)
The government had reduced fertilizer subsidy since 1st April 2010, which increased fertilizer price by 25-40%. Fertilizer price is predicted to further increasing, thus farmers must be more efficient in using fertilizer for their rice field. Landholding for rice farmers in Indonesia is mostly small and varying. Farming practices vary among farmers and among fields, therefore crop needs for nutrient inputs vary greatly among fields. For this reason we are suggesting the need for the formulation of up to three types of NPK fertilizers for rice in Indonesia: (a) NPK source with ratio about 1:1:1 as in Phonska, (b) NK source for application as topdressing to obtain high yield on land without application of crop residues and organic matter, or K soil is deficient, and (c) NP source with 1:1 ratio for N:P, for use in situation where yield was low and high application of crop residues or organic matter, or high soil supply of K. IAARD in collaboration with IRRI had developed the Nutrient Manager for Rice, an interactive computer-based decision tool, which provides fertilizer guideline for a rice field, based on the response to easy-to-answer multiple choice questions. The web application of Nutrient Manager for Rice for Indonesia was released by Minister of Agriculture and could be accessed through http://webapps.irri.org/nm/id. It became evident that extension workers could be reached faster through internet to improve their knowledge for fertilizer management in Indonesia. The target users are (a) AIAT extensionist, (b) field extension, and (c) progress farmers. With SSNM technology, it is expected that the use of fertilizer by farmers it more rational, and at the same time increase rice production as well as farmers incomes.